Effects of Geranyloxycinnamic Acids on COX‐2 and iNOS Functionalities in LPS‐Stimulated U937 Mononuclear Cells. Issue 17 (25th October 2016) - Genovese, Salvatore; Fiorito, Serena; Taddeo, Vito Alessandro; Epifano, Francesco; Paciotti, Roberto; Coletti, Cecilia; Franceschelli, Sara; Speranza, Lorenza; Ferrone, Alessio; Felaco, Mario; Patruno, Antonia
Abstract: A series of naturally occurring and semisynthetic O ‐geranyl cinnamic acids and their conjugates with the i NOS inhibitor N ω ‐nitro‐L‐arginine methyl ester have been synthesized and evaluated for their effects on expressions of COX‐2 and i NOS, antioxidant activity, and PGE2 and NO production in LPS‐stimulated U937 mononuclear cells. All adducts showed little or no effect on i NOS functionality in terms of NO release. A much more significant activity has been recorded on PGE2 biosynthesis for which the sample substituted with a ‐NO2 group in position 3 of the aromatic ring revealed an effect in the nM range both for the L‐NAME conjugated product and the parent compound (IC50 =0.71 μM and 0.1 μM respectively). Preliminary docking studies have been carried out to clarify the mechanism of COX‐2 inhibition, and they suggest that the geranyloxy side chain is likely to play an important role for the observed activity and that structural modifications are able to tune such effects. Abstract : Natural and semisynthetic 4′‐geranyloxycinnamic acid derivatives and their codrugs with the i NOS inhibitor L‐NAME have been tested as in vitro anti‐inflammatory agents. The acid having a nitro group in position 3 of the aromatic ring and its coupling product displayed a very interesting inhibitory activity on PGE2 biosynthesis with IC50 in the nanomolar range. Docking studies revealed the pivotal role of the geranyloxy side chain as a determinant for an effective COX‐2 inhibition.